Konsep Hard Skill, Soft Skill Dan Spiritual Skill Pustakawan Menghadapi Era Library 3.0 - Rotmianto, Mohamad (Pustakaloka, 2015)
InÂ  thisÂ  presentÂ  time,Â  librarianÂ  mustÂ  knowÂ  wellÂ  about information technology orÂ  it also called have aÂ  literacy ofÂ  information technology.Â  BecauseÂ  theyÂ  (librarian)Â  willÂ  faceÂ  theÂ  âexplosionÂ  of informationâ, as well as a newÂ  library user named âNet Generationâ who wants all information to be presented more accurate, quicker and interactively, as the demands of Library 3.0. Mastery three skills: hard skillÂ  (IQ)Â  andÂ  softÂ  skillÂ  (EQÂ Â  )Â  combinedÂ  withÂ  spiritualÂ  skillÂ  (SQ)Â  is requiredÂ  toÂ  succeedÂ  to be a Librarian 3.0,Â  so not only qualifedÂ  inÂ  the feld of technology, but more than that librarians also have a humanism side that is based on religious principles.